Efficacy of endoscopic vacuum therapy in esophageal luminal defects: a systematic review and meta-analysis - Ishaan Vohra; Harishankar Gopakumar; Neil R. Sharma; Srinivas R. Puli (Clinical Endoscopy)
Background/Aims Endoscopic vacuum-assisted closure (EVAC) is a novel technique used to repair esophageal perforation and leaks. Varying data have been reported on the overall success rate of EVAC. We aimed to conduct a meta-analysis of the available data on the clinical success rate of EVAC. Methods Electronic databases were searched for publications addressing the efficacy of EVAC in esophageal luminal defects. Pooling was conducted using both fixed and random-effects models. The overall clinical success of EVAC therapy was considered the primary outcome, whereas, overall complication rates, need for adjunct therapy, and mortality were considered secondary outcomes. Results In total, 366 patients were included in the study. On pooled analysis, the mean age was 66 years with 68.32% of patients being men. Overall pooled clinical success rate of EVAC therapy was 87.95%. Upon subgroup analysis, the pooled clinical success rate of postsurgical anastomotic leak and transmural esophageal perforation were found to be 86.57% and 88.89%, respectively. The all-cause hospital mortality was 14% and 4.2% in patients with esophageal perforation and EVAC, respectively. Conclusions This study demonstrates that EVAC therapy has a high overall clinical success rate, with low mortality. EVAC therapy seems to be a promising procedure with excellent outcomes in patients with luminal esophageal defects.